Exploring barriers to early breast examination and screening among Arab women in the MENA region: A KAP study - Ehsan Qtaishat; Reem Al-Ajlouni; Khawlah Ammar; Mohammed Liswi; Abdallah Al-Ani; Rasha Fakheraldeen; Shorouq Al-hasson (Heliyon)
Aim: To examine the knowledge, attitudes, and practices (KAP) regarding early breast cancer screening among women across the MENA region. Methodology: This cross-sectional investigation deployed a survey designed to investigate women's KAP with regards to breast cancer signs and symptoms, early breast cancer detection methods, sources of knowledge, and barriers towards early detection exams. The survey was distributed over social media platforms during the period between June 2022–September 2022. Responses were reported as frequencies and analyzed per the participants demographic characteristics. Results: A total 2681 Arab women were included in the final analysis. Sudan (31.3 %), Saudi Arabia (15.6 %), and Palestine (14.0 %) were the most represented countries. Only 53.4 % of participants were able to recognize at least 5 signs and symptoms of breast cancer. While family history was the most reported risk factor for breast cancer (85.6 %), early onset of menarche (23.0 %) and late onset of menopause (24.0 %) were the least recognized. Participants were well aware of self-breast examination (SBE) with 72.0 % practicing it on regular basis. Conversely, while nearly half of the sample practices clinical breast examinations (CBE) or mammography (MM), less than 50 % were knowledgeable abouts their proper frequencies or suitable age. In terms of barriers, lack of current breast issues and lack of knowledge were the most commonly reported barriers to all three forms of early breast cancer detection methods. Univariate analysis demonstrated that regularly practicing SBE and CBE were associated with higher knowledge of breast cancer signs and symptoms (all p < 0.05). Also, older participants were more likely to be aware and be regularly compliant with SBE, CBE, and MM (all p < 0.001). Area of residence did not impact knowledge or practices of early breast cancer detection methods. Conclusion: Among our population of sampled adult Arab women, knowledge of breast cancer, its risk factors, and early detection methods are not satisfactory. Thus, we recommend increased awareness efforts and a profound exploration of the effectiveness of such interventions.